2014
DOI: 10.1007/s00405-014-3137-9
|View full text |Cite
|
Sign up to set email alerts
|

The bonebridge as a transcutaneous bone conduction hearing system: preliminary surgical and audiological results in children and adolescents

Abstract: The Bonebridge (®) (BB, Med-El) is a newly designed transcutaneous active bone conductive implant with functional outcome similar to percutaneous bone-anchored hearing systems (BAHS). It is currently approved only for patients ≥18 years. Since the BB allows the skin to remain intact and therefore should be able to overcome some of the issues related to percutaneous BAHS including skin reactions, wound infection and implant extrusion, it would be especially attractive for use in children. We present a prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 18 publications
7
33
1
1
Order By: Relevance
“…24 Furthermore, the mean speech recognition thresholds were reduced after implantation when both speech and noise were presented from the front. 28 However, Laske et al state that speech perception was not improved in patients with single-sided deafness in the speech and noise presented from the front condition irrespective of the use of a Bonebridge device. 27 The improvement of speech-to-noise ratio was not statistically significant in the speech and noise presented from the front, and speech and noise presented from the front and contralateral (normal ear) side separately conditions in this study, which is in contrast to that shown in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…24 Furthermore, the mean speech recognition thresholds were reduced after implantation when both speech and noise were presented from the front. 28 However, Laske et al state that speech perception was not improved in patients with single-sided deafness in the speech and noise presented from the front condition irrespective of the use of a Bonebridge device. 27 The improvement of speech-to-noise ratio was not statistically significant in the speech and noise presented from the front, and speech and noise presented from the front and contralateral (normal ear) side separately conditions in this study, which is in contrast to that shown in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups around the world have reported different audiological results (functional gain, speech reception thresholds, and word recognition scores). 2 3 4 6 8 Based on our experience, 90% of patients with conductive hearing loss got the total closure of air-bone gap, which means a gain of 30 to 60dB. In cases of congenital atresia, this is achieved in almost all patients, being less prevalent in patients with other etiologies, such as otosclerosis or chronic otitis media.…”
Section: Data Synthesismentioning
confidence: 97%
“…The Bonebridge is currently approved only for patients 18 years of age or older. However, Hassepass et al [24] reported a straightforward surgical procedure and satisfactory functional gain after TBCI surgery in an adolescent patient ≥ 12 years old. Baumgartner et al [6] also demonstrated the safety and efficacy of the Bonebridge implant in a 5-year-old child.…”
Section: Discussionmentioning
confidence: 99%